"Don't Just Tell Me the Answer": Ethnicity, Gender and Parents' Science Scaffolding. Issue 1 (1st January 2022) - Short-Meyerson, Katherine; Sandrin, Susannah; Meyerson, Peter; White, Lindsey
ABSTRACT: This study examines interactions of fourth graders and their parents during informal science activities to understand the parental influence on children's science interests, attitudes, and participation. Sixteen Latino/a parent–child dyads and 16 Non-Latino/a parent–child dyads, matched on socioeconomic status (SES), participated in this qualitative study. Content analysis elucidated themes including parental intrusive support, aiming for deeper understanding, questioning by parents and children, language challenges, parent and child affect, and parent-dominated, child-dominated, or collaborative problem solving. Potential differences in cultural context and gender biases are explored and approaches to parental outreach and enrichment are discussed.